Identification of T-DNA structure and insertion site in transgenic crops using targeted capture sequencing - Magembe, Eric Maina; Li, Hui; Taheri, Ali; Zhou, Suping; Ghislain, Marc (Frontiers in Plant Science, 2023)
Genetically engineered (GE) crops must go through a pre-market safety assessment to ensure they are safe for humans, animals, and the environment. The molecular characterization of the T-DNA insertion is a critical step for selecting a transgenic event bearing a T-DNA with all transgenes intact, without multiple full or partial copies of it, and with an insertion into a known region of the crop genome. This has long been a tedious process using multiple PCR techniques and Sanger sequencing methods, which limits the number of transgenic events that can be assessed.